The Effects of Platelet Rich Plasma Topical Gel on Chronic Plantar Ulcer Healing in Leprosy Patient - Diana Kartika Sari; M. Yulianto Listiawan; Diah Mira Indramaya (Faculty of Medicine, Universitas Airlangga, 2016)
Background: Plantar ulcer is a physical disability that most often occurs in approximately 10-20% of leprosy patient. Conventional therapies such as dressings, surgical debridement, and skin graft can not provide satisfactory improvement. Platelet rich plasma (PRP) has a variety of growth factors required in ulcer wound healing. Purpose: To prove the effect of PRP topical gel to the size of wound, macrophage activation, neovascularization, fibrosis, and formation of granulation tissue on chronic plantar ulcer healing in leprosy patients. Methods: The analytic cohort study of 20 leprosy patients with chronic plantar ulcer in Morbus Hansen Division, Dermatology and Venereology Outpatient Clinic, Dr. Soetomo Hospital Surabaya. Biopsies were performed before and after PRP topical gel treatment on leprosy patient with chronic plantar ulcers. Results: After two doses of PRP topical gel, wound size of 9 patients (45%) was reduced <0.5 cm. Statistycal analysis showed significant differences in size of lesions (p = <0.05), the number of macrophages (p = <0.001), number of capillaries (p = 0.003), and the amount of granulation (p = 0.032) before and after PRP topical gel treatment. While the results of the analysis of the number of fibroblasts showed no significant difference (p = <0.05). Conclusion: PRP topical gel treatment gives good results, in terms of improvement in wound size, an increase in macrophages, neovascularization and granulation tissue.